Pediatric extremity rhabdomyosarcoma–A diagnostic dilemma (Indian Journal of Case Reports, 2024)
Rhabdomyosarcoma (RMS) is a common soft-tissue malignancy of childhood, accounting for approximately 7% of cancers in children. They arise from primitive mesenchymal cells of skeletal muscle differentiation and occur most commonly in the head-and-neck region. Despite aggressive approaches, the overall outcome remains poor. Here, we present the case of a 9-year-old girl who presented with complaints of swelling over the left forearm for 2 months. Magnetic resonance imaging revealed a well-defined lobulated mass in the flexor compartment of the left forearm, suggestive of soft-tissue neoplasm. A biopsy done of the mass showed a malignant round blue cell tumor. Immunohistochemistry led to the diagnosis of RMS. The patient was started on multimodal therapy and is doing well on follow-up. Extremity swelling in the pediatric age group with malignant round cell morphology can pose diagnostic difficulty. A detailed work-up is essential for an accurate diagnosis. This case report emphasizes the role of a multimodality approach to the diagnosis and treatment of pediatric RMS.